Komunikasi Islam Inklusif dalam Politik Dakwah Sjafruddin Prawiranegara (1911-1988) - Hasan Mustapa; Andi Faisal Bakti (Jurnal Komunikasi Islam, 2021)
Religion is frequently presented as a source of conflict in a plural society on the political stage. In truth, the essence of goodness may be found in every religious teaching, including Islam. To alleviate tensions between two cultural communities, one’s ability to express religiously inclusive messages to other parties is critical. This paper examines how Sjafruddin Prawiranegara interprets inclusive Islamic values both philosophically and practically. Using a qualitative approach and intercultural communication perspective, this studi has revealed that Sjafruddin intends to portray Islam as accepting and beneficial, with pleasant and appreciating contacts with individuals of the same religion or different religions.